2002
DOI: 10.1051/0004-6361:20020923
|View full text |Cite
|
Sign up to set email alerts
|

New measurements of orbital period change in Cygnus X-3

Abstract: Abstract. The nonlinear nature of the binary ephemeris of Cygnus X-3 indicates either a change in the orbital period or an apsidal motion of the orbit. We have made extended observations of Cygnus X-3 with the Pointed Proportional Counters (PPCs) of the Indian X-ray Astronomy Experiment (IXAE) during 1999 July 3−13 and October 11−14. Using the data from these observations and the archival data from ROSAT, ASCA, BeppoSAX and RXTE, we have extended the database for this source. Adding these new arrival time meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(97 citation statements)
references
References 20 publications
3
93
1
Order By: Relevance
“…The 4.8 h X-ray light curve has shown a remarkable stability in terms of its shape (Ghosh et al 1981) and the period has shown a gradual increase at a rate of ∼10 −9 s s −1 . Recently, Singh et al (2002) have extended the span of the observation and have concluded that the period change is consistent with a constant rate of 5.76 ± 0.24 × 10 −10 . Remarkably, the binary modulation was also found to be consistent with the template derived from the EXOSAT data (van der Klis & Bonnet-Bidaud 1989).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The 4.8 h X-ray light curve has shown a remarkable stability in terms of its shape (Ghosh et al 1981) and the period has shown a gradual increase at a rate of ∼10 −9 s s −1 . Recently, Singh et al (2002) have extended the span of the observation and have concluded that the period change is consistent with a constant rate of 5.76 ± 0.24 × 10 −10 . Remarkably, the binary modulation was also found to be consistent with the template derived from the EXOSAT data (van der Klis & Bonnet-Bidaud 1989).…”
Section: Introductionmentioning
confidence: 86%
“…Recently, Singh et al (2002) have extended the data base of the binary period measurements using the Indian X-ray Astronomy Experiment (IXAE) and archival data from ROSAT, ASCA, BeppoSAX and RXTE. They found that the binary template obtained from the EXOSAT data adequately explains the recent observations and have derived a value of the period derivative of 5.76 ± 0.24 × 10 −10 .…”
Section: Binary Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ephemeris of Singh et al (2002) was used to compute the orbits. The data were limited to moderately high states (daily means ≥15 counts/s), to be more consistent with the Cygnus X-3 spectral state during the Chandra/HETG observations used.…”
Section: Modeling Of the X-ray Continuum And Emission Line Light Curvesmentioning
confidence: 99%